Dissolving alkali metals in zeolites: Genesis of the perfect cluster crystal - Woodall, L; Anderson, P; Armstrong, A; Edwards, P (1996)
The interaction of alkali metals with dehydrated zeolites Y and A leads, in a process which bears many similarities to the dissolution of those metals in non-aqueous liquid solvemts, to the formation of inclusion compounds which may be regarded as ordered arrays of closely spaced clusters, and whose properties are dependent on interactions between the clusters. A combined analysis of electron spin resonance, magnetic susceptibility and powder neutron diffraction results enabled us to follow in detail the chemistry behind the formation of sodium- and potassium-based 'cluster crystals' in zeolites Y and A respectively.